The Cytokinin-Activating LOG-Family Proteins Are Not Lysine Decarboxylases. Issue 4 (April 2018) - Naseem, Muhammad; Bencurova, Elena; Dandekar, Thomas
Abstract : A conserved PGGxGTxxE motif misleads the cytokinin (CK) converting LONELY GUY enzymes to be wrongly annotated as lysine decarboxylases (LDCs). However, so far PGGxGTxxE motif-containing LDCs do not show any LDC activity. Instead, they show phosphoribohydrolase activity by converting inactive CK nucleotides into active free-base forms to invoke CK responses.